1999
DOI: 10.1016/s0014-5793(99)00184-2
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of the carboxy‐terminal domain of RNA polymerase II for the transcriptional activation of chromosomal c‐fos and hsp70A genes

Abstract: The carboxy-terminal domain of the large subunit of mouse and human RNA polymerase II contains 52 repeats of a heptapeptide which are the targets for a variety of kinases. We have used an K K-amanitin resistant form of the large subunit of pol II to study the role of the carboxy-terminal domain in the expression of chromosomal genes. The large subunit of RNA polymerase II and deletion mutants thereof, which contain only 31 (LSv v31) and 5 (LSv v5) repeats, were expressed in 293 cells. Subsequently, the endogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
(31 reference statements)
3
8
0
Order By: Relevance
“…Mapping of the 5Ј-end of RNAs demonstrated that pol II 1-22, pol II 31-52, and pol II 1-52 all initiated transcription at the expected position. As expected from previous reports (Gerber et al 1995;Okamoto et al 1996;Meininghaus and Eick 1999), pol II lacking a CTD (pol II ⌬) did not transcribe RNA from this minigene reporter (Fig. 2B, lane 1).…”
Section: Analysis Of the Ctd Requirement In Mrna Processingsupporting
confidence: 91%
See 1 more Smart Citation
“…Mapping of the 5Ј-end of RNAs demonstrated that pol II 1-22, pol II 31-52, and pol II 1-52 all initiated transcription at the expected position. As expected from previous reports (Gerber et al 1995;Okamoto et al 1996;Meininghaus and Eick 1999), pol II lacking a CTD (pol II ⌬) did not transcribe RNA from this minigene reporter (Fig. 2B, lane 1).…”
Section: Analysis Of the Ctd Requirement In Mrna Processingsupporting
confidence: 91%
“…Truncation of the CTD in yeast and mammals reduces activator-dependent stimulation of transcription of some genes (Allison and Ingles 1989;Gerber et al 1995;Meininghaus and Eick 1999). Moreover, differential phosphorylation of the CTD correlates with steps in the transcription cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Deletion of CTD Affects Initiation of pol II-We have shown previously that transiently expressed LS*wt but not LS*⌬5 is able to induce expression of the hsp70A and c-fos genes in 293 cells after appropriate stimuli (51). We confirmed this observation for Raji cells.…”
Section: Conditional Expression Of the Large Subunit Of Pol Ii-supporting
confidence: 80%
“…In this model, gene activity is primarily controlled by chromatin state and PIC assembly. Promoter-proximal pausing in eukaryotes was characterized at Drosophila major heat shock genes 19,20,112 , and similar analyses revealed human c-myc and c-fos genes appeared to have a similar promoter-proximal pausing [113][114][115] . This mode of regulation was initially considered by the field to be a regulatory step that was specific to a few highly-inducible genes; however, studies tracking nascent RNA synthesis, together with other methods, including genome-wide ChIP-and PIP-seq 67 , demonstrated that promoter-proximal pausing is widespread throughout metazoan genomes 17,18,22,23,44,46,51,55,67,[116][117][118] (reviewed in Refs.…”
Section: Gene Activation Is Defined By Initiation and Promoter-proximal Pausingmentioning
confidence: 99%